Understanding automotive electronics : an engineering perspective - Ribbens, William B. (Butterworth-Heinemann, 2013)
Understanding Automotive Electronics is the first port of call for control engineers, system engineers and electronic engineers in automotive needing a thorough grounding in automotive electronics and control. From simple automotive electronic circuits to latest developments in telematics, active safety, entertainment and communications, the book is also an ideal resource for more senior automotive engineers without a background in electronics or control needing to work in the area or supervise specialists. Thoroughly updated throughout, this new edition moves away from introductory mechanic-level electronics to cover hot topics such as transmission control, hybrid control, AUTOSAR (AUTomotive Open System ARchitecture) and vehicle networks. Comprehensive coverage of automotive electronics and control, including the latest technology in telematics, active safety, entertainment and communicationsCovers the topic from an engineering perspective rather than a technician or mechanic-focused trouble-shooting levelIdeal as a conversion tool for control and electronic engineers moving into the automotive industry and a valuable reference for all automotive engineers without an electronics background needing to understand this far-reaching topic.
Previous edition published as: Understanding automotive electronics / by William B. Ribbens, 2003.
Includes index.
Keywords: Automobiles -- Electronic equipment.; elektronické knihy; electronic books